Approximations to fixed points of contraction semigroups in hilbert spaces - Xu, Hong-Kun (Numerical functional analysis and optimization, 1998)
Sequences (or curves) are constructed to approximate common fixed points of a pair of nonex-pansive mappings (or contraction semigroups) in Hilbert spaces. The obtained results extend the previously known results from a single mapping to a family of mappings.